A comparison of muscle stiffness and musculoarticular stiffness of the knee joint in young athletic males and females. Issue 3 (June 2015) - Wang, Dan; De Vito, Giuseppe; Ditroilo, Massimiliano; Fong, Daniel T.P.; Delahunt, Eamonn
Abstract The objective of this study was to investigate the gender-specific differences in peak torque (PT), muscle stiffness (MS) and musculoarticular stiffness (MAS) of the knee joints in a young active population. Twenty-two male and twenty-two female recreational athletes participated. PT of the knee joint extensor musculature was assessed on an isokinetic dynamometer, MS of the vastus lateralis (VL) muscle was measured in both relaxed and contracted conditions, and knee joint MAS was quantified using the free oscillation technique. Significant gender differences were observed for all dependent variables. Females demonstrated less normalized PT (mean difference (MD) = 0.4 N m/kg, p = 0.005, η2 = 0.17), relaxed MS (MD = 94.2 N/m, p < .001, η2 = 0.53), contracted MS (MD = 162.7 N/m, p < .001, η2 = 0.53) and MAS (MD = 422.1 N/m, p < .001, η2 = 0.23) than males. MAS increased linearly with the external load in both genders with males demonstrating a significantly higher slope (p = 0.019) than females. The observed differences outlined above may contribute to the higher knee joint injury incidence and prevalence in females when compared to males.